Justice-Involved Children with Special Educational Needs and Disability: What Are the Implications for Access to Identification and Support Through an Education, Health and Care Plan? A Thought Piece - Tristan Middleton (Social Sciences)
This thought piece exposes the gap in the operationalised support in England for young people within the justice system who have special educational needs and disabilities. It exposes inequity within the system which serves to create barriers for justice-involved young people, who are likely to already be disengaged from education, in accessing appropriate provision. It presents gaps in key educational advice and practice relating to access to Education, Health and Care Plans as a route to support for justice-involved young people, identifying a negative bias for this group of children who are already marginalised. Within the context of an English Special Educational Needs system which is widely recognised as broken, and an ongoing parliamentary consultation into ways to improve the situation, this piece suggests key changes to reduce the inequitable access to special education provision for young people accommodated in the secure estate. These suggestions make a contribution to the agenda of English politicians and the Department of Education.